Cytomegalovirus infection and risk of preeclampsia: A meta-analysis of observational studies - Zahra Geraili; Seyed Mohammad Riahi; Soghra Khani; Masomeh Bayani; Ali Rostami; Karimollah Hajian-Tilaki; Malihe Nourollahpour Shiadeh (Babol University of Medical Sciences, 2018)
Background: Cytomegalovirus (CMV) infection is one of the most common infectious diseases in pregnant women in terms of global impact and is related with many adverse health consequences during pregnancy. For the first time, we performed a systematic review and meta-analysis study to evaluate the possible association between CMV infection and preeclampsia (PE). Methods: A comprehensive literature search to identify the relevant papers published earlier than February 2018 was performed in PubMed, ISI (Web of Science), Google Scholar and SCOPUS databases. We followed the PRISMA (preferred reporting items for systematic reviews and meta-analyses) guidelines for design, analysis and interpretation of results.  Pooled odds ratio (OR) and 95% confidence intervals (CI) were estimated using a random-effects meta-analysis model. Heterogeneity was assessed with Q-test and I2 statistics. Results: A total of 13 studies including 6158 pregnant women (2734 women with PE and 3424 healthy controls) met the eligibility criteria. The results of meta-analyses based on PCR (OR: 3.09; 95% CI:0.72–13.24; I2=57.3%), IgG-ELISA (OR: 1.24; 95% CI:0.83–1.85; I2=71%) and IgM-ELISA (OR: 1.04; 95% CI:0.66–1.65; I2=0.0%) demonstrated that CMV infection could not be a potential risk factor for PE. Conclusions: In conclusion, results of the present study demonstrated that CMV infection could not be a potential risk for developing PE. More epidemiological and experimental studies are needed to investigate the impact of CMV infection on the development of PE.